CARBON COMPOSITE MATERIALS AS IMPLANTS FOR ORTHOPEDICS AND TRAUMATOLOGY. (literature review) - Чорний, Владислав (SWorldJournal, 2023)
In traumatology and orthopedics, the understanding of osteosynthesis combines the study of the physical and physiological properties of the human support apparatus and the configuration and material science of implants. The main directions of the developm